Marketing strategies of five-star hotels in Singapore - Tan, Wang Shing (2014)
Although the hotel industry is an important sector in Singapore's economy, not much research has been done. In fact, not much research has been done on the service sector as a whole, except for the banking industry. The primary objective of this study is to find out the current strategies applied by the five-star hotels in Singapore and their immediate problems. As the hotel industry is currently in the mature phase of its industry life cycle, it is of much benefit for the hotels to apply the correct marketing strategy in order to carve out a niche in the industry and to compete domestically and internationally. This is especially so for the luxurious five-star hotels, where future supply is more than adequate in meeting demand (now that the Four Seasons Hotel has opened).